Morphological examination of the effects of defibrotide on experimentally induced bladder injury and its relation to interstitial cystitis - ERCAN, FERİHA (SPRINGER, 2001)
This morphological study aims to investigate the effects of defibrotide, a deoxyribonucleic acid derivative drug with cytoprotective, immuno suppressive and vasorelaxant effects, on protamine sulfate induced bladder injury. Wistar albino female rats were catheterized and intravesically infused with phosphate buffered solution (control group) or, either protamine sulfate (bladder injury group) or protamine sulfate+defibrotide (bladder injury+defibrotide group) dissolved in phosphate buffered solution. The morphology of the urinary bladder was investigated using light and electron microscopy. The number of mast cells in the mucosa, mucosal alterations, intercellular junctions, surface topography and the glycosaminoglycan (GAG) layer as well as microvillus formation on the luminal surface were evaluated. In the bladder injury group, ulcerated areas, irregularity of the GAG layer, increased number of mast cells, vacuole formation, dilated perinuclear cistern, formation of pleomorphic and uniform microvilli and dilatations in the intercellular spaces in the urothelium were observed. In the bladder injury+defibrotide group a relatively normal urothelial topography, GAG layer and a few mast cells in the mucosa, some dilatations between the intercellular areas, less uniform microvilli, regular perinuclear cistern and tight junctions were observed. These results show that defibrotide can inhibit PS induced bladder damage.
Keywords: protamine sulfate; defibrotide; urinary bladder; interstitial cystitis; ultrastructure; EPITHELIAL PERMEABILITY BARRIER; SURFACE GLYCOSAMINOGLYCANS; VASCULAR DISORDERS; PROTAMINE SULFATE; URINARY-BLADDER; REPERFUSION; PROTECTION; ACTIVATION; STRESS; AGENT